Work characteristics as predictors of physiological recovery on weekends - Berset, Martial; Semmer, Norbert K.; Elfering, Achim; Amstad, Fabienne T.; Jacobshagen, Nicola (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVES ': 'This study investigated whether work characteristics predict physiological recovery on a rest day. Specifically, we aimed to show that high demands and low control at work would lead to higher cortisol values and thus poor recovery on a rest day. ' ' METHODS ': 'A total of 69 individuals participated in this study. In addition to analyzing questionnaire responses, we measured salivary cortisol on two workdays and on a subsequent rest day (a Sunday). We used multiple regression analysis. We controlled for the workday cortisol level; results reflect the relative change in cortisol from workday to rest day. In addition, we controlled for gender, since this relates to cortisol levels at work. ' ' RESULTS ': 'We found that control at the workplace predicted cortisol levels on a rest day. Specifically, individuals with less job control had higher cortisol levels, and consequently poorer recovery on the rest day than those with more control. Neither job demands nor the interaction of demands and control predicted a change in cortisol levels from workday to rest day. ' ' CONCLUSIONS ': 'The results indicated that a lack of control at work impairs physiological recovery on the weekend, one of the central recuperation periods. In light of the potential importance of incomplete recovery with respect to long-term ill health, it should be considered crucial to ensure job control at the workplace.
Keywords: cortisol; job control; job demand; physiological recovery; stress; unwinding; weekend; work characteristic; work stress